Analgesic Mechanisms of Steroid Ointment against Oral Ulcerative Mucositis in a Rat Model - Mako Naniwa (MDPI AG, 2021)
Despite the long history of use of steroid ointments for oral mucositis, the analgesic mechanism has not been fully elucidated. In this study, we examined the effects of triamcinolone acetonide (Tmc) on oral ulcerative mucositis-induced pain in conscious rats by our proprietary assay system. Based on evaluations of the physical properties and retention periods in the oral mucosa of human volunteers and rats, we selected TRAFUL® ointment as a long-lasting base. In oral ulcerative mucositis model rats, TRAFUL® with Tmc suppressed cyclooxygenase-dependent inflammatory responses with upregulations of glucocorticoid receptor-induced anti-inflammatory genes and inhibited spontaneous nociceptive behavior. When an ointment with a shorter residual period was used, the effects of Tmc were not elicited or were induced to a lesser extent. Importantly, TRAFUL® with Tmc also improved oral ulcerative mucositis-induced mechanical allodynia, which has been reported to be independent of cyclooxygenase. Ca2+ imaging in dissociated trigeminal ganglion neurons showed that long-term preincubation with Tmc inhibited the hypertonic stimulation-induced Ca2+ response. These results suggest that the representative steroid Tmc suppresses oral ulcerative mucositis-induced pain by general anti-inflammatory actions and inhibits mechanical sensitivity in peripheral nerves. For drug delivery, long-lasting ointments such as TRAFUL® are needed to sufficiently induce the therapeutic effects.